2021
DOI: 10.1093/jac/dkab201
|View full text |Cite
|
Sign up to set email alerts
|

PBP4-mediated β-lactam resistance among clinical strains of Staphylococcus aureus

Abstract: Background PBP4, a low-molecular-weight PBP in Staphylococcus aureus, is not considered to be a classical mediator of β-lactam resistance. Previous studies carried out by our group with laboratory strains of S. aureus demonstrated the ability of PBP4 to produce β-lactam resistance through mutations associated with the pbp4 promoter and/or gene. Recent studies of β-lactam-resistant clinical isolates of S. aureus have reported similar mutations associated with pbp4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
5
12
1
Order By: Relevance
“…The wild-type strain as well as the strains with promoter-associated mutations all had similar growth patterns in absence of β-lactams (Figure 1f). Taken together, these results suggested that promoterassociated mutations led to PBP4 overexpression and β-lactam resistance in MRSA background, similar to what was previously demonstrated in MSSA background strains (7,13).…”
Section: Pbp4 Promoter-associated Mutations Led To Increased Pbp4 Exp...supporting
confidence: 88%
See 4 more Smart Citations
“…The wild-type strain as well as the strains with promoter-associated mutations all had similar growth patterns in absence of β-lactams (Figure 1f). Taken together, these results suggested that promoterassociated mutations led to PBP4 overexpression and β-lactam resistance in MRSA background, similar to what was previously demonstrated in MSSA background strains (7,13).…”
Section: Pbp4 Promoter-associated Mutations Led To Increased Pbp4 Exp...supporting
confidence: 88%
“…These studies were performed by introducing promoter-associated mutations into strains devoid of mecA . Using allelic replacement, we created isogenic mutants by introducing three different, previously detected mutations in the pbp4 promoter region of SF8300 (13, 17). Of these, two mutations were detected in laboratory-generated resistant strains as a result of a passaging experiment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations